EVALUATION OF THE ARABIC TEACHING IN THE CONTEXT OF THE BASIC DYNAMICS IN MADRASAS AND FACULTIES OF DIVINITY - İbrahim USTA (Fırat University, 2019)
In this study the comparision of Arabic teaching in the madrasas and in Faculties of Arabic will be made in the context of basic dynamics such as aim, content, process, assessment and evaluation and the similar and different aspects of the two education system will be evaluated briefly. Some proposals are suggested at the end of the subject.